Occupational Stress in Service Sector Among Women Employees In Tirunelveli District (International Journal of Food and Nutritional Sciences, 2021)
Stress is a common feature in our lives, especially as the pace of development increases. Work is a common term which is applied for all sorts of occupation. Stressful situations in the workplace are a common incidence for all employees especially for the Women. Stress from any source may affect an employee’s well-being and their performance at work. The service sector consists of the soft parts of the economy such as insurance, government, tourism, banking, retail, education, and social services. Now-adays Women working in all the categories of work. So, they are getting stress from working places. In it, an occupational stress can be caused by too much or too little work, time pressure and deadlines, fatigue from physical strains of work environment, excessive travelling, long hours, having to cope with changes in work. This study focuses about the Occupational Stress in Service Sector among the Women Employees in Tirunelveli District. There many sectors doing their works. Due to, lack of time the researcher finds four service sectors only like Education, Banking, Insurance Hospitality and so on. For that, the researcher collected 80 samples by convenient sampling method and used percentage and chi-square test applied for this research.